Models and Modeling
VIII, 292 p.
Keywords: The process of developing models, known as modeling, allows scientists to visualize difficult concepts, explain complex phenomena and clarify intricate theories. In recent years, science educators have greatly increased their use of modeling in teaching, especially real-time dynamic modeling, which is central to a scientific investigation. Modeling in science teaching is being used in an array of fields, everything from primary sciences to tertiary chemistry to college physics, and it is sure to play an increasing role in the future of education. Models and Modeling: Cognitive Tools for Scientific Enquiry is a comprehensive introduction to the use of models and modeling in science education. It identifies and describes many different modeling tools and presents recent applications of modeling as a cognitive tool for scientific enquiry. The processes of modelling and the use of the resulting models to inform predictions play key roles in the nature of science and hence in science education, especially in inquiry-based approaches. Against a background of the philosophical basis for modelling and models, the implications for science education are explored. Well-designed and thoroughly classroom-tested schemes to support students in learning how to model are reviewed. Research into teachers’ understanding of models and their place in the nature of science are reviewed as are successful strategies for the further development of that knowledge. This book has a major contribution to make to the pre- and in-service education of elementary (primary) and high (secondary) school science teachers. John K. Gilbert Professor Emeritus, The University of Reading Visiting Professor, King's College London Editor-in-Chief, International Journal of ScienceEducation.